Q&A - Ask Doubts and Get Answers
Q

Factorise the following expressions (l + m) ^2 - 4 lm

Q1 Factorise the following expressions 

(VII)

( l+m ) ^2 - 4lm

Answers (1)
Views

We have, 
               ( l+m ) ^2 - 4lm = l^{2} + 2ml + m^{2} - 4lm                                         (using \ (a+b)^{2} = a^{2} + 2ab + b^{2})
                                                = l^{2} - 2lm + m^{2} 
                                                = (l-m)^{2}                                                                   (using \ (a-b)^{2} = a^{_2} -2ab + b^{2})
                                                                                                  

Exams
Articles
Questions